A proposed AI-based educational program for developing geographic virtual tour design skills and technological engagement among education faculty students - Elsayed, Mohamed Farag; Abodonia, Abdelgawad Hassan; Farrag, Amal Khaled; Kelany, Ahmed Abdelsalam; Abdelnabi, Ihab Nafad (International Journal of Innovative Research and Scientific Studies, 2025)
Geographic education faces significant challenges in engaging contemporary students and integrating emerging technologies effectively. This study aimed to evaluate the effectiveness of an AI-based educational program designed to develop geographic virtual tour design skills and enhance technological engagement. A quasi-experimental design with pre-test and post-test measurements was employed with 60 fourth-year geography students from Al-Azhar University. The AI-based educational program was developed using the ADDIE instructional design model. Participants’ performance was assessed using three instruments: Geographic Virtual Tour Design Skills Achievement Test (GVTDS-AT), Geographic Virtual Tour Design Skills Performance Observation (GVTDS-PO), and a Technological Engagement Scale. Results revealed statistically significant improvements (p < 0.01) across all measured variables, with very large effect sizes ranging from 3.30 to 17.32. Theoretical knowledge scores increased from 19.88 to 59.18 (Cohen’s d = 7.20), while practical performance improved from 27.91 to 99.78 (Cohen’s d = 9.41). All technological engagement dimensions showed substantial improvements, with the total engagement score increasing from 74.51 to 173.23 (Cohen’s d = 17.32). These findings demonstrate that AI-based educational programs can effectively enhance both geographic virtual tour design competencies and technological engagement, modernizing geographic education and preparing future educators with essential digital skills.